PENGARUH FRAUD DIAMOND BAGI KECURANGAN PENGELOLAAN KEUANGAN DESA - Sri Puspita Sari; Kartika Kartika; Whedy Prasetyo (Universitas Jember, 2020)
This study aims to show and explain how the picture of fraud can occur in the government sector, especially in the village government sector in Sidoarjo sub-district. This study uses data collection techniques in the form of primary data by distributing questionnaires. The research analysis method used is descriptive statistics, data quality test, classic assumption test and hypothesis testing consisting of multiple linear regression methods, f test, t test, and coefficient of determination. The results of this study indicate that there is a significant negative effect between the suitability of compensation, internal control systems and organizational culture for fraud. As for the competency, it has a significant positive result of fraud on the village government in Sidoarjo sub-district. Keywords: Disclosure, Heritage Assets, Recognition, Valuation